Generalization and modelling of rigid polyisocyanurate foam reaction kinetics, structural units effect, and cell configuration mechanism - Xu, Jie; Wu, Tao; Sun, Wei; Peng, Chuang (Smithers Rapra, 2017)
PIR/PUR ratio was derived from differential manipulation of generalized polyisocyanurate kinetic model. The structural unit effects on polymerization of isocyanurate, urethane and urea linkages were evaluated based on Mayo-Lewise tercopolymerization scheme. The cell microstructural configuration model was further developed from profiled FOAMAT reactivity parameters with integrated analysis of cell interface physics. The interstitial border area was defined by interface free energy theory, the shear viscosity was evaluated by foam motion, gas fraction, and partial pressure, and the cell inflation was re-examined by gas-liquid surface tension variability. The cell anisotropic degree, assumed as an aspect ratio of infinitesimal volume elements in cell uniformity, was characterized by equilibrated work increase of surface energy approximated by 2D stretching deformation from sphere cell to spheroid cell. The relationship between pressure and surface tension of elongated cells was also derived from modelling at the same condition of cell deformation.